2020
DOI: 10.1590/0001-3765202020181203
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR-1273g-3p acts as a potential biomarker for early Breast Ductal Cancer diagnosis

Abstract: Circulating miRNAs presenting in plasma in a stable manner have been demonstrated their potential role as a promising biomarkers in many human diseases, such as Alzheimer's disease, melanoma and ovarian carcinoma. However, few circulating miRNAs could be used for breast ductal cancer diagnosis. Here, we identified miR-1273g-3p as a biomarker for detecting breast ductal cancer. We detected miR-1273g-3p levels in the plasma of 39 sporadic breast ductal cancer patients and 40 healthy donors by Stemloop Quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…miR-1273 g has been linked to breast cancer [ 138 , 139 ] and radiation treatments of cancer [ 140 ]. However, no clinical studies have reported a link with cardiovascular diseases and therefore, this microRNA is not currently considered informative for cardiotoxicity in breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…miR-1273 g has been linked to breast cancer [ 138 , 139 ] and radiation treatments of cancer [ 140 ]. However, no clinical studies have reported a link with cardiovascular diseases and therefore, this microRNA is not currently considered informative for cardiotoxicity in breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 16 142 articles were identified in the aforementioned databases (Table 1). However, 234 articles were retained for full reading, following the elimination of duplicates and articles whose title and abstract did not meet the eligibility criteria; of these, only 136 12…”
Section: Resultsmentioning
confidence: 99%
“…miRNAs have gained increasing relevance because of their functions in the growth of cancer cells such as hyperplasia and migration [8]. In recent years, several studies including the research of Papachristopoulou et al [13] and Guo et al [14] illuminated the potential relationship between miRNA and breast tumors, while their researches only clarify the role of one particular miRNA in breast neoplasms. For other correlative studies, they paid more attention on the relationship between clinicopathological characteristics and miRNAs [15,16].…”
Section: Discussionmentioning
confidence: 99%